Mathematics Anxiety and Its Relationship with Form Four Students’ Achievement in the Klang District, Malaysia - Davrajoo, Elenchothy (2007)
The aim of this study was to identify the level of Mathematics anxiety and its relationship with form four students’ achievement in Klang district. The study involved a sample of 182 male and 160 female students (n = 342) from ten daily schools in the Klang district. The Students Mathematics Anxiety Scale (SKMP) was used to measure mathematics anxiety level. This exploratory research used design method of descriptive statistics (mean, standard deviation, frequency and percentage) and inferential statistics (t-test, one way ANOVA, correlation Pearson r, Spearman’s rho multiple regressions) to analyze the data. Findings showed that the level of students mathematics anxiety were on moderate level (mean = 2.37; SD = 0.74). In details, all the underlying dimensions of mathematics anxiety, that are class climate (mean = 2.03; SP = 0.78), incapability (mean = 2.41; SP = 0.76), abstraction of mathematics (mean = 2.33; SP = 0.86), and mathematics achievement test (mean = 2.65; SP = 0.97) on moderate level. The findings showed that 52.9% of respondents had experienced the physical symptoms during the mathematical situations in moderate level. Analyses on perceptions of mathematics showed value of mathematics (mean = 1.74; SD = 0.79), self confidence (mean = 3.42; SD = 1.05) and enjoyment of mathematics (mean = 3.17; SD = 1.04) in mathematical situations were low. Study also showed there was a significant relationship between students’ perception and their mathematics anxiety (r = 0.50). In detail enjoyment of mathematics (r = 0.43), self confidence in mathematical situations (r = 0.40) and value of mathematics (r = 0.21) showed a moderate relationship with mathematics anxiety. The findings have shown there was a significant relationship between mathematics anxiety and the occurring of physical symptoms during the mathematical situations (r = 0.61). An analysis of variance among groups of pure science (n = 117), technical science (n = 111) and humanities science (n = 114), revealed that these groups differed significantly (F (2,339) = 8.38, p < 0.05). The findings of a one-way ANOVA indicated a significant difference between science humanities group with pure science group and the science technical group respectively. Yet a no significant difference was found between the According to the findings several suggestions were suggested to school, Education Ministry and future research. As a outcomes, the study can be used as a resource in planning and implementing quality teaching and learning of mathematics. This aspect should be instilled in the teaching approach in order to enhance the quality of teaching and learning in secondary school especially the schools in rural area.